ATTITUDES AND COMMUNITY READINESS TOWARD DIGITAL TOURISM DEVELOPMENT - Tumiar Sidauruk; Fitra Delita; Rohani; Elfayetti; Herdi (Jurnal Masyarakat dan Budaya, 2023)
The tourism industry is growing along with technological developments and human needs. In fact, tourism is the main economic sector in several countries, including Indonesia. Tourism development requires the full support of the local community in a tourist destination. The purposes of this study were to analyze people's attitudes towards the impact of tourism and measure community readiness towards digital tourism development in Pangururan Subdistrict, Samosir Regency. Data were collected using questionnaires and interviews. Respondents were local people and community leaders with a total of 79 people. Quantitative data were analyzed using descriptive statistics and qualitative data through qualitative deductive analysis of content. The results of the study showed the positive attitude of the community towards the impact of tourism in both socio-cultural, economic and environmental aspects. The highest mean value was on economic impact. Community readiness for digital tourism development consists of 6 dimensions, namely community knowledge about the issue, resources related to the issue, community efforts, community knowledge of the efforts, leadership and community climate. The highest mean was on leadership at preparation level. But overall, the community's readiness for the development of digital tourism is at the preplanning level.